The Implementation of STEM-Integrated Project-Based Learning (Pjbl) to Improve Students' Critical Thinking Skills - Tania Avianda Gusman; Sodikin Sodikin; Mutiara Dwi Cahyani (FKIP - Universitas Riau, 2026)
This study addresses the low level of students’ critical thinking skills in chemistry learning, particularly in the context of thermochemistry, which is an abstract and complex concept to visualize. To overcome this challenge, Project-Based Learning (PBL) was integrated with the STEM (Science, Technology, Engineering, and Mathematics) approach. The research aimed to examine the improvement of students’ critical thinking skills and to explore their responses toward the PjBL-STEM model. A quantitative experimental method was employed with purposive sampling of 11th-grade senior high school students. Research instruments included a critical thinking test based on Facione’s indicators, observation sheets, and student response questionnaires. The data were analyzed using both descriptive and inferential statistical techniques. The findings revealed a significant improvement, with the average score increasing from 47% in the pre-test to 74% in the post-test. Students showed better performance in interpretation, analysis, evaluation, inference, explanation, and self-regulation. Furthermore, responses toward the PjBL-STEM model were highly positive, with 67% of students agreeing and 21% strongly agreeing with its implementation. These results suggest that PjBL-STEM provides a practical, interactive, and contextual learning experience, thereby enhancing students’ critical thinking skills in chemistry education.